Pengaruh Remitansi Masuk terhadap Pertumbuhan Ekonomi dan Kemiskinan di Kota Ambon - Laitupa, Abdul Azis; Niapele, Sarifa; Jani, Jani; Siahainenia, Silfiena (Jurusan Ekonomi Pembangunan, FEB Universitas Pattimura, 2025)
This study aims to determine the effect of incoming remittances on economic growth and poverty in Ambon City. Remittance receipts are one of the largest contributors to economic growth and tend to be more stable (Jawaid & Raza, 2012). In addition, the flow of remittance funds is also an important source of state revenue for developing countries (Soava, et al., 2020). (2020). In several studies that have been conducted, remittance receipts have been a major factor in rapid economic growth in several developing countries. The World Bank (2005) generally explains that remittances are transfers of funds made by migrant workers to recipients in their home countries. The data used is secondary data, namely the number of incoming remittances, the poor population and economic growth. The results showed a negative relationship between incoming remittances and poverty and a positive relationship between incoming remittances and economic growth. Meanwhile, poverty and economic growth have a negative relationship. Efforts to encourage increased growth in remittance inflows that have been made by the government should be carried out on an ongoing basis. an integral part of the policy of increasing foreign exchange.